2015
DOI: 10.1103/physrevd.92.083528
|View full text |Cite
|
Sign up to set email alerts
|

Heating of baryons due to scattering with dark matter during the dark ages

Abstract: We explore the effects of elastic scattering between dark matter and baryons on the 21-cm signal during the dark ages. In particular, we consider a dark-matter-baryon interaction with a cross section of the form σ = σ0v −4 , in which case the effect of the drag force between the dark mater and baryon fluids grows with time. We show that, as opposed to what was previously thought, this effect heats up the baryons due to the relative velocity between dark matter and baryons. This creates an additional source of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
238
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(250 citation statements)
references
References 62 publications
(102 reference statements)
9
238
3
Order By: Relevance
“…The evolution equations of temperature and relative velocity were given in Ref. [46]. Focusing on n ¼ −4 scattering, we show in Fig.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution equations of temperature and relative velocity were given in Ref. [46]. Focusing on n ¼ −4 scattering, we show in Fig.…”
Section: Figmentioning
confidence: 99%
“…The authors of Ref. [46] showed that DM-baryon scattering can also heat both fluids under the right circumstances, from friction due to their relative velocity; this effect is more important for heavier DM, above 1 GeV in mass.…”
Section: Characterizing Mass Dependence In the Cmb Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is motivated by the EDGES measurement of the 21-cm spectrum at z ≃ 17, which revealed an anomalously large absorption signal [34,35] (see also Refs. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]). The SENSEI constraint (orange) is bounded by the solid (dashed) line for small (large)σ e .…”
mentioning
confidence: 99%
“…Because the intensity of the detected signal is proportional to I 21 cm ∝ 1 − ðT R ðzÞ=T S ðzÞÞ, where T S is the spin temperature of the atomic hydrogen and T R is the temperature of background radiation, the very first studies of the EDGES anomaly ascribed the extra absorption to a new cooling mechanism for the hydrogen gas, based on baryon-dark matter (DM) interactions [2][3][4][5][6][7] (this idea was studied before the EDGES anomaly appeared in Refs. [8][9][10]), on modified onset of star formation [11,12], or on the effects of dark energy [13,14]. DM annihilations [15][16][17] and black hole accretion [18], however, result in the injection of particles characterized by a broad energy spectrum that inevitably lead to heating the hydrogen clouds.…”
Section: Introductionmentioning
confidence: 99%